Simultaneous Recruitment of Stem Cells and Chondrocytes Induced by a Functionalized Self-Assembling Peptide Hydrogel Improves Endogenous Cartilage Regeneration - Lv, Xiao; Sun, Caixia; Hu, Binwu; Chen, Songfeng; Wang, Zhe; Wu, Qiang; Fu, Kun; Xia, Zhidao; Shao, Zengwu; Wang, Baichuan (Frontiers in Cell and Developmental Biology, 2020)
The goal of treating articular cartilage (AC) injury is to regenerate cartilage tissue and to integrate the neo-cartilage with surrounding host cartilage. However, most current studies tend to focus on engineering cartilage; interface integration has been somewhat neglected. An endogenous regenerative strategy that simultaneously increases the recruitment of bone marrow mesenchymal stem cells (BMSCs) and chondrocytes may improve interface integration and cartilage regeneration. In this study, a novel functionalized self-assembling peptide hydrogel (KLD-12/KLD-12-LPP, KLPP) containing link protein N-peptide (LPP) was designed to optimize cartilage repair. KLPP hydrogel was characterized using transmission electron microscopy (TEM) and rheometry. KLPP hydrogel shared a similar microstructure to KLD-12 hydrogel which possesses a nanostructure with a fiber diameter of 25–35 nm. In vitro experiments showed that KLPP hydrogel had little cytotoxicity, and significantly induced chondrocyte migration and increased BMSC migration compared to KLD-12 hydrogel. In vivo results showed that defects treated with KLPP hydrogel had higher overall International Cartilage Repair Society (ICRS) scores, Safranin-O staining scores and cumulative histology scores than untreated defects or defects treated with KLD-12 hydrogel, although defects treated with KLD-12 and KLPP hydrogels received similar type II collagen immunostaining scores. All these findings indicated that the simple injectable functionalized self-assembling peptide hydrogel KLPP facilitated simultaneous recruitment of endogenous chondrocytes and BMSCs to promote interface integration and improve cartilage regeneration, holding great potential as a one-step surgery strategy for endogenous cartilage repair.